PERBEDAAN PENGARUH BRIDGING DAN QUADRUPED POSITION WITH LOWER EKSTREMITY LIFT EXERCISE DENGAN UNILATERAL BRIDGE DAN PRONE BRIDGE EXERCISE TERHADAP FUNGSIONAL BERDIRI PADA ANAK CEREBRAL PALSY SPASTIK DIPLEGI - Sari Tri Yulianti (Jurnal Ilmiah Fisioterapi, 2019)
Background: Cerebral Palsy (CP) is the most common form of physical disability in childhood, it caused by a static lession in the immature brain. CP spastic diplegic is one of the most common clinical subtypes of CP that lower limbs are more severely affected than the upper limbs. Different methods have been used to improve standing function in children with CP spasic diplegic, but still little is known regarding the effect of trunk strengthening exercise on standing function in children with CP spastic diplegic. This study aims to compare the effect of bridging and quadruped position with lower extremity lift exercise versus unilateral bridge and prone bridge exercise on standing function in children with CP spastic diplegic. Methods: An experimental study with pre and post test design on 10 children with CP spastic diplegic, ages 8 to 13 years. The children were divided into 2 groups: (1) group treated with bridging and quadruped position with lower extremity lift exercise (Group-1), (2) group treated with unilateral bridge and prone bridge exercise (Group-2). The treatments were given for 6 weeks, 3 days per week. Standing function was measured by Gross Motor Function Measurement (GMFM). Results: The result showed that there were significant differences on standing function in Group-1 (p=0,001) and Group-2 (p=0,002), but there were no significant differences on standing function between Group-1 and Group-2 (p=0,302). Conclusion: There were no differences between the group treated with bridging & quadruped position with lower extremity lift exercise and group treated with unilateral bridge & prone bridge exercise on standing function in children with CP spastic diplegic.